REDESAIN BUKU MENU KAFE CUBITCX SEBAGAI MEDIA INFORMASI - Fitriandary, Kartika; Hindraruminggar, Rika (Anggada : Jurnal Desain dan Seni, 2021)
Development of information tecnology not only has changed societies’ lifestyle, but also impacted on high-end looking cafés, and one of them is CubitCX café which is situated in Mustika Jaya, Bekasi. Selling kinds of desserts and drinks, the feminine and unique concept isn’t much supported by its menu design. The only solution that could be offered is to do redesign with the goal of increasing the design’s effectiveness, both visually and technically. This design is intended to target the café’s common guests, which are teenagers and young adults. Data were collected by interviews with the café owner and waiters, then references were collected both from printed and digital media.This design is expected to give postive images for the guests, provide clear and correct visual that eventually will increase the guests’ brand awareness, and the order will take shorter duration and therefore effective.